The Role of the Internet in Developing the Professional Performance of English Teachers in General Secondary Education Schools in Lattakia City (Journal of Hama University, 2020)
The aim of the present research is to identify the role of the Internet in developing the professional performance of English teachers in the general secondary schools in Lattakia from their point of view.To achieve the research objective, the researcher applied a questionnaire which included (30) items addressed to English teachers. On the sample of (75) teachers and schools, the results of the research showed that the mean averages ranged between (2.46 - 3.95), and that the second area (interaction with others) obtained a large level, where the average grade (3.95) The first area (class management) and the third area (activities and evaluation) were obtained at an intermediate level with a mean average of (2.45) (3.55). The results of the study showed that there are statistically significant differences between the average estimates of teachers of the research sample on the total score of the tool according to the educational qualification variable. There were no statistically significant differences between the average of the teachers' estimates of the research sample on the total score of the tool according to the variable of years of experience. The researcher presented a set of proposals, including providing teachers of English language with theoretical knowledge about the importance of using the Internet in their work to improve the educational process and development